How to increase the attractiveness of undergraduate rural clerkships? A cross-sectional study among medical students at two German medical schools. Issue 6 (25th June 2021) - Herget, Sabine; Nafziger, Melanie; Sauer, Stephanie; Bleckwenn, Markus; Frese, Thomas; Deutsch, Tobias
Abstract : Objectives: While literature provides substantial evidence that undergraduate rural clerkships may contribute to attract medical students to rural careers, so far little is known about how to convince medical students to choose rural teaching sites for their clerkships, which is usually optional. Thus, this study aimed to investigate students' preferences and perceptions regarding different rural teaching and clerkship formats, important side conditions and suitable communication strategies to promote rural clerkships. Design: Cross-sectional study based on a quantitative survey among medical students in advanced study years. Setting: Two German medical schools (Leipzig and Halle-Wittenberg). Participants: Medical students in third to fifth year (of six). Results: Response rate was 87.1% with n=909 analysable questionnaires. Participants' mean age was 25.0 years and 65.2% were women. For 97.9% of the students completing some kind of rural clerkship was imaginable, for 90.8% even participation in a rural clerkship of 4 weeks and longer. Nearly half of the students (48.0%) specified that a rural clerkship 4 weeks and longer was 'absolutely imaginable'. Younger age, having grown up in a rural or small-town region, being able to imagine future working in a small-town or rural area, and general practice as favoured, or at least conceivable career option were independently associated with a higher willingness to complete longer rural clerkships. Financial and organisational issues including remuneration of the clerkship, cost absorption for travelling and accommodation, and accessibility by public transport were the most important side conditions to increase the attractiveness of rural clerkships. Experience reports by fellow students, social media and informational events were stated to be the most suitable ways to advertise rural teaching offers. Conclusions: The majority of the students are open-minded regarding even longer rural clerkships. This study adds new insights into measures that should be taken to convince them to actually chose this option.